Developing medical oncology in Africa - Busakhala, Naftali (Ecancermedicalscience, 2019)
BACKGROUND: Kenya, like most other developing countries, is undergoing an epidemiologic shift of disease patterns characterized by an increasing prevalence of cancer and other non-communicable diseases straining health care resources which were mainly intended for communicable diseases. We describe the development of sustainable cancer prevention and control programs at Moi University and Moi Teaching and Referral Hospital in Western Kenya. METHODS: The cancer prevention and control program at Moi Teaching and Referral Hospital was started by volunteer nurses and clinicians in 2005 in response to a high prevalence of AIDS-related Kaposi sarcoma. Chemotherapy was donated by a local drug store until 2007 when Eli Lilly pharmaceuticals from Indianapolis in the USA started helping the program through the Academic Model Providing Access to Healthcare (AMPATH). Due to good response rates of patients with AIDS-related Kaposi sarcoma, and lobbying by volunteers, the service became a formal department of Moi Teaching and Referral hospital in 2008. RESULTS: The department has now grown to become the second largest public cancer centre in the country registering about 9000 patient visits per year. In addition, staff have now specialized in various areas such as medical oncology, palliative care, surgical oncology, nursing and gynaecology oncology. CONCLUSIONS: The development of a medical oncology program requires a multi-disciplinary team focused on integration within existing programs and expansion of collaborative networks in order to provide the best care to patients.